1992
DOI: 10.1541/ieejias.112.613
|View full text |Cite
|
Sign up to set email alerts
|

Digital Current Control Method of Induction Motor Using Synchronous Current Detection with PWM Signal.

Abstract: This paper proposes a fully digital current control method with DSP for the vector control of the induction motor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…It is shown that the expansion and modularization characteristics of the CHBM inverter are improved when using Phase-Shifted Pulse Width Modulation (PSPWM) since the individual inverter modules operate more independently. However, the PSPWM of a CHBM has a phase difference between the reference voltage and real voltage, which can cause instability in the current controller at high speeds where the ratio of the sampling frequency to the output frequency is insufficient [12]- [14]. This instability in the current controller is removed by adding the proposed method which compensates for the phase difference between reference voltage and real voltage.…”
Section: Control For High Performance a Voltage Delay Compensatmentioning
confidence: 99%
“…It is shown that the expansion and modularization characteristics of the CHBM inverter are improved when using Phase-Shifted Pulse Width Modulation (PSPWM) since the individual inverter modules operate more independently. However, the PSPWM of a CHBM has a phase difference between the reference voltage and real voltage, which can cause instability in the current controller at high speeds where the ratio of the sampling frequency to the output frequency is insufficient [12]- [14]. This instability in the current controller is removed by adding the proposed method which compensates for the phase difference between reference voltage and real voltage.…”
Section: Control For High Performance a Voltage Delay Compensatmentioning
confidence: 99%
“…DPWM reduces the average switching frequency by 33% compared with CPWM and moreover if 60" intervals of no switching region is distributed to positive and negative peak of the phase current, the switching loss can be further minimized[ 111. If there is no time delay between the real current and the sampled one, it is well known that the sampled current represents the fundamental component of the motor current [5]. But if some delay is introduced, the above statement is invalid.…”
Section: Modelling Of Current Measurement Delaymentioning
confidence: 99%
“…Assuming that the system delay is constant as (2) and is sufficiently small, the measurement error in DPWM is given by (5). where AI& = 1 :…”
Section: A Derivation Of Sampling Errormentioning
confidence: 99%
See 1 more Smart Citation